2004
DOI: 10.1007/s11103-004-4953-x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a blueprint for UDP-glucose pyrophosphorylase structure/function properties: homology-modeling analyses

Abstract: UDP-glucose pyrophosphorylase (UGPase) is an important enzyme of synthesis of sucrose, cellulose, and several other polysaccharides in all plants. The protein is evolutionarily conserved among eukaryotes, but has little relation, aside from its catalytic reaction, to UGPases of prokaryotic origin. Using protein homology modeling strategy, 3D structures for barley, poplar, and Arabidopsis UGPases have been derived, based on recently published crystal structure of human UDP-N-acetylglucosamine pyrophosphorylase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
(71 reference statements)
1
33
0
Order By: Relevance
“…An in depth homology analysis carried out recently to reveal evolutionary relatedness showed that all eukaryotic UGPs isolated from plant, animal, yeast, and slime mold form separate but tightly linked clades in a parsimony tree (38). In contrast, the prokaryotic UGPs form a distinct clade showing no significant sequence homology to eukaryotic UGPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in depth homology analysis carried out recently to reveal evolutionary relatedness showed that all eukaryotic UGPs isolated from plant, animal, yeast, and slime mold form separate but tightly linked clades in a parsimony tree (38). In contrast, the prokaryotic UGPs form a distinct clade showing no significant sequence homology to eukaryotic UGPs.…”
Section: Discussionmentioning
confidence: 99%
“…This regulatory mechanism received confirmation by the resolution of the crystal structure of the closely related human UDP-Glc(Gal)NAc pyrophosphorylase (AGX (29)). The AGX protein, which crystallized as a dimer in the presence of its products UDP-GlcNAc or UDP-GalNAc, was used as a template for three-dimensional homology models of the barley, poplar, and A. thaliana UGPs (38). In accord with the template, the obtained hypothetical structures suggest that dimerization and/or oligomerization leads to sterically hindered access to the substrate binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, comparison of amino acid sequences of the melon UGPase with other plant UGPases indicates a very high homology with no indication of a significant change in the sugar binding site of the melon enzyme that would indicate that its substrate specificity would be unique. Recently, Geisler et al (2004) carefully homology-modeled the three-dimensional (3-D) structure of plant UGPase. The homology comparisons between the melon sequence and the modeled sequences indicate a few otherwise conserved amino acids that are not conserved in the melon sequence (replacements of the following, according to the melon sequence: I154V, Y180F, V234I, Q238K Q293E, and I334V), but based on the 3-D homology modeling these amino acid differences are unlikely to play a role in the reaction that might alter or extend the melon enzyme substrate specificity to uniquely include UDP-Gal.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the model of UGPase structure (Geisler et al, 2004) indicates that the respective amino acids in the corresponding b-sheet are NLW in place of NIA of the AGX1, and that the large hydrophobic Trp in the UGPase NLW sequence may indeed impede the equatorial Gal 4OH, explaining the specificity for Glu-P for this enzyme. We attempted to show that this is the case by performing a site-directed mutagenesis of the UGPase W to N. We hypothesized that the modified UGPase would be capable of metabolizing Gal-1-P.…”
mentioning
confidence: 87%
“…We have recently shown that several compounds, identified by screening a small molecule chemical library, served as potent UDP-glucose pyrophosphorylase (UGPase) and UDP-sugar pyrophosphorylase (USPase) inhibitors, and that some of them were also effective in in vivo studies 5 . The identified inhibitors were inhibiting both UGPase and USPase activities, possibly reflecting common structural features at or near active sites of these enzymes 6 , 7 . Dose-response studies revealed that the identified inhibitors had IC 50 values in the µM-range against each of the target enzymes 5 …”
mentioning
confidence: 99%